7 LEARNING FROM THE FALLS ANALYSIS OF OLDER PEOPLE ADMITTED TO AN IRISH POST-ACUTE REHABILITATION SERVICE. (25th October 2022) - Reynolds, A; Landers, R
Abstract: Background: Thirty percent of community-dwelling older adults fall each year with 10% suffering a severe injury often resulting in hospital admission. To deliver effective falls prevention a thorough falls history is required. The objective of this study was to complete a SPLATT (symptoms before fall, previous falls, location of fall, activity at time of fall, time of day and trauma sustained) analysis of falls that resulted in an acute hospital admission reported by older people on admission to the post-acute rehabilitation unit. Methods: Older people admitted to rehabilitation post fall that resulted in acute admission were included in this study. The SPLATT analysis was completed on OT initial assessment. Data was anonymized and recorded using Microsoft excel. Results: A total of 61 falls were included in the analysis. Participants were all older people admitted to post-acute rehabilitation (female= 48, male= 13). 93% reported no symptoms before their fall. Almost half (43%) had experienced previous falls. Most falls (51%) happened at home with most of these (29%) occurring in the bedroom. A significant proportion (30%) happened in the community. The most common cause of fall was a loss of balance (32%) while completing a reaching or functional task. Most falls (87%) happened during the day but of those who fell at night, 62.5% occurred while trying to use the toilet. The majority (82%) of the falls lead to a significant trauma – hip fracture. Conclusion: The results of this study supports that falls prevention interventions for rehabilitation service users should incorporate functional training both at home and in the community. The individual SPLATT analysis could support the design of a falls prevention intervention tailored to the person's needs and history.